Fiber optic cabling - Elliott, Barry J.
Essential reading for anyone involved in fiber optic cable applications, from installation engineers to IT professionals. Fiber Optic Cabling is a practical guide to all aspects of designing, specifying and installing systems for LANs and other data communications applications. The second edition has been completely revised and updated by Barry Elliott, taking into account the major developments in LAN and transmission technology over the past 10 years. The latest legislation is also dealt with, including standards relating to flammability. Cutting edge topics such as photonic switching, wavel.